Coffee ring elimination and crystalline control of electrohydrodynamically printed high-viscosity perovskites. Issue 47 (9th October 2019) - Li, Hegeng; Liu, Nian; Shao, Zhilong; Li, Huayang; Xiao, Lin; Bian, Jing; Li, Jinghui; Tan, Zhifang; Zhu, Menghua; Duan, Yongqing; Gao, Liang; Niu, Guangda; et al.
Abstract : This work combined a high-viscosity perovskite precursor with PVP and EHD printing to fabricate high-resolution microarrays with perfect morphologies. Abstract : Lead halide perovskites show enormous potential for display because of their tunable emission, high color purity, strong photoluminescence and electroluminescence. However, it is a huge challenge to achieve high resolution patterning with perfect crystalline morphologies of perovskite crystals. In this work, we combine a high-viscosity perovskite precursor with polyvinylpyrrolidone (PVP) and powerful electrohydrodynamic (EHD) printing to fabricate in situ crystallized high-resolution microarrays with perfect morphologies. Adding PVP contributes to reducing capillary flow to eliminate coffee rings and form spatial confinement during evaporation, limiting the flow of ions and the size of perovskite grains. However, it increases the solution viscosity, which makes printing rather difficult. This problem is solved by introducing EHD printing, which has superior advantages in high-viscosity ink printing and high-resolution patterning. Through collaborative optimization of the printing and crystallization process, the as-printed patterns and luminous images show satisfactory uniformity and high controllability in micron dimensions, and exhibit excellent compatibility with flexible substrates. This strategy is promising for wide-ranging types of optoelectronic devices.